1-2-sinf o‗quvchilarining jismoniy tayyorgarligini «salomatlik» testlari yordamida baholash - Uraimov, S.R (SCIENCE and SOCIETY, 2023)
The relationship between sensitive periods and motor skills was studied in 1-2 graders, and the role of adaptability in the development of the organism was shown. During the annual educational cycle, a pedagogical experiment was conducted using "Health" health tests to monitor the dynamics of movement qualities in children of primary school age.
Keywords: "Health" test; pedagogical experience; pedagogical control; ontogenesis; adaptive abilities; speed-strength physical qualities; physical activity; physical training; physical fitness